Determination of the adrenomedullin gene variations in patients with coronary artery disease: Evaluation of the ADM gene in coronary artery disease - Çolak Geniş, Esra; Batır, Muhammet Burak; Gerik-Çelebi, Hamide Betül; Çam, Fethi Sırrı (Journal of Surgery and Medicine, 2025)
Background/Aim: Coronary artery disease is characterized by atherosclerosis in the vessel wall. The protein encoded by the adrenomedullin (ADM; OMIM No. 103275) gene is a preprohormone, post-translationally modified to form two biologically active peptides. These peptides are involved in a myriad of functions including vasodilation, bronchodilation, regulation of hormone secretion, growth modulation, promotion of angiogenesis, and antimicrobial activity. This study was designed to explore the correlation between the development of atherosclerosis and variations in the ADM gene. Methods: The study analyzed 62 cases with atheromatous plaques and 46 cases without such plaques. Genomic DNA was extracted from peripheral blood. Variations in the ADM gene were determined by Sanger sequencing. Results: In this study, four different variants were found in the ADM gene, including c.-2140T>C (rs3814700), c.248+91T>G (rs545190978), c.150C>G (rs5005), and c.261C>T (rs767028428 C>T). The allele frequencies of these ADM gene polymorphisms in patients were as follows: T at 93% and C at 7% for rs3814700 (T>C); T at 99.2% and G at 0.08% for rs545190978 (T>G); C at 99.2% and G at 0.08% for rs5005 (C>G); and C at 99.2% and T at 0.08% for rs767028428 (C>T). Conclusion: It was found that there was no significant difference in allele frequencies and genotypes of these polymorphic regions between the patients and the control group.